AB1179 Failure of adalimumab treatment in three patients with papa syndrome. (23rd January 2014) - Finetti, M.; Omenetti, A.; Caorsi, R.; Federici, S.; Buoncompagni, A.; Marotto, D.; Jorini, M.; Naselli, A.; Picco, P.; Martini, A.; Gattorno, M.
Abstract : Background: Pyogenic sterile arthritis, pyoderma gangrenosum and acne (PAPA) syndrome is a rare autosomal dominant autoinflammatory disorder due to mutations in the CD2 binding protein 1 (CD2BP1) gene. This syndrome is featured by pyoderma gangrenosum, cystic acne and recurrent pyogenic sterile arthritis, with increased serological acute phase reactants during active disease. However, the clinical presentation and response to treatment display significant individual variability. The therapeutic approach during recurrences consists of steroids, while no agreement exists on the chronic management. Recent evidence suggests the possible use of anti-TNFα monoclonal antibodies (Punaro et al.), while the efficacy of Adalimumab (IgG1 humanized monoclonal anti-TNFα antibody) has been described only in a few cases and not yet proven. Objectives: To evaluate the response to treatment with Adalimumab (IgG1 humanized monoclonal anti-TNFα antibody) in 3 PAPA patients followed in a single Center. Methods: Three patients (M:F=2:1, mean age 13 years, range 5-22 years) with a molecular diagnosis of PAPA syndrome (mutations E256G, E250K, E250Q) were enrolled and treated with Adalimumab (patients#1-2: 40 mg/15 days, patient#3: 20 mg/15 days). Results: Clinical outcomes evaluated were the frequency of articular and cutaneous flares in the 12 months before starting therapy compared to those occurred during Adalimumab regimen, whereas laboratory tests (ESR, PCR) were assessed at the last visit before the study enrolment and at end of treatment. Patient#1 (F, E256G+) presented both articular and cutaneous involvement. During the 25 months of treatment, she had only mild decrease in the frequency of articular recurrences (3 episodes/year before vs 1 episode/year after treatment) and pyoderma gangrenosum episodes (12 episodes/year before vs 4 episodes/year after treatment); however, a worsening size of the cutaneous lesions occurred, requiring surgical removal in one occasion. Patient#2 (M, E250K+) displayed only cutaneous involvement in the 12 months before starting Adalimumab administration, with persistent pyoderma gangrenosum on the left arms. Following the treatment period (3 months), he showed the persistence of the lesion, without clinical improvement. Reactivation of the articular symptoms was not observed. Patient#3 (M, E250Q+) was affected by recurrent arthritis localized to left elbow, ankles and knees, without cutaneous involvement. During the 9 months of treatment, he didn't show any clinical improvement, with no significant changes in the frequency of articular episodes (10 episodes/year before vs 8 episodes/year after treatment). No difference in the levels of acute phase reactants were observed for all three patients before and after Adalimumab treatment. Conclusions: Taken together, these findings suggest that our cohort of PAPA patients didn't gain any benefit from Adalimumab administration, nor at clinical or serological level. Thus, further research is needed in order to explore novel therapeutic approaches. Disclosure of Interest: None Declared